From Europe to Tripoli in Barbary via Istanbul: the Municipality and reforms in an Outpost of the Ottoman Empire (1868-1911) - (:unkn) unknown (My University, 2003)
A discussion of the "importation" paradigm in the circulation of urban reform models between Europe and the Ottoman Empire. A research based upon a study of local archives in Tripoli and central ottoman archives in Istanbul.
Keywords: African Research